COMPUTED TOMOGRAPHY FOR FORAMEN OVALE EVALUATION - KURDO, HAVEEN HAJI; ALI , SOHAIB HASAN; SAEED, MAYSALOON SHAMAN (Journal of Duhok University, 2023)
Introduction: Foramen ovale (FO) is a significant foramen located in the greater wing of the sphenoid bone, It is one of the foramen that form the base of the skull, which is an important anatomic structure of the skull’s anatomy. Computed tomography (CT) is used to evaluate the foramen ovale. Objectives: The axial plane of computed tomography was utilized to measure the foramen ovale’s dimensions (length and width) and observe the variations in its shape. Patients and Methodes: A total of one hundred foramen ovale were evaluated from fifty computed tomographies (CTs). The axial image shows the bilateral FO of one patient. The length and width on both sides were measured. The information was gathered from the radiology department at Vajeen Private Hospital in Duhok, Kurdistan, Iraq.By using the RadiAnt DICOM viewer, we measured the anterioposterior diameter (length), transverse diameter (width), and shape of the foramen ovale on both sides. The significant level of difference was determined by a p-value <0.05. Results: The mean (SD) length of the foramen ovale on the right side was 6.98 (1.04) mm and on the left side was 6.83 (1.10) mm, and the mean width of foramen ovale was 3.87 (0.78) mm on the right side and 4.16 (0.70) mm on the left side. The foramen ovale was typically oval in 63 cases (28 on the right and 35 on the left), almond in 15 cases (11 on the right and 4 on the left), irregular in 14 cases (9 on the right and 5 on the left), and round in 8 cases (2 right, 6 left). Conclusion: Variations are commonly seen in the dimensions of the foramen ovale, which is usually used in different diagnostic and therapeutic procedures. The width of the foramen ovale significantly differed between the left and right sides (P<0.05), although the length of the ovale did not differ significantly (P > 0.05). Comparing this study to other research, there was no visible variation in the foramen ovale’s shape.